On the economics of refugee flows - Oded Stark (Institute for Advanced Studies (IHS), 2003)
Although the phenomenon of refugee flows is not devoid of economic connotations, it has so far been investigated primarily by political scientists and sociologists. The analytical tools of economic inquiry have not yet been applied to this subject, although it stands to reason that such a study will contribute to our understanding of why refugee flows occur and will guide the policy response. This note illustrates how economic analysis can be brought to bear on three key aspects of refugee flows: fear, poverty, and group movement.
Keywords: A11; F02; J24; 330; refugee flows; group movement; impoverishment and fear; Internationale Wanderung; Flüchtlinge; Theorie